An outbreak of monophasic Salmonella Typhimurium associated with raw pork sausage and other pork products, Denmark 2018–19. (2019) - Helmuth, I. G.; Espenhain, L.; Ethelberg, S.; Jensen, T.; Kjeldgaard, J.; Litrup, E.; Schjørring, S.; Müller, L.
Abstract: In Denmark, outbreaks of salmonella with more than 20 cases have become rare. In November 2018, an outbreak of monophasic Salmonella Typhimurium was detected and an investigation initiated with the aim of identifying the source and controlling the outbreak. Outbreak cases were defined based on core genome multilocus sequence types. We conducted hypothesis-generating interviews, a matched case-control study, food sampling and trace-back investigations. We identified 49 cases distributed across Denmark. In univariable analyses a traditional form of raw Danish pork sausage (medister sausage), pork chops and ground veal/pork showed matched odds ratio of 26 (95% CI 3–207), 4 (95% CI 1–13) and 4 (95% CI 1–10), respectively. In a multivariable analysis, only medister sausage remained significant. Several patients described tasting or eating the sausage raw or undercooked. Samples of medister sausage analysed were negative for salmonella and investigations at the production site did not reveal the mechanism of contamination. In conclusion, in spite of having eliminated salmonella in the egg and broiler industry, Denmark is still at risk of major salmonella outbreaks. We identified a raw pork sausage as a particular risk product that needs to be thoroughly cooked before consumption. Tasting raw meat or eating undercooked pork should be discouraged.